Pengaruh Konsentrasi Benziladenin (BA) pada Pertumbuhan Spatifilum (Spathyphyllum wallisii) - Rugayah, Rugayah; Nurrahmawati, Nurrahmawati; Hendarto, Kus; Ermawati, . (Universitas Lampung, 2021)
Spatifilum (Spathiphyllum wallisii) is a popular ornamental plant that can be used as indoor decoration, so its appearance should be attractive. Apart from flowering, an interesting criteria for the appearance of the spatula is to have many tillers so that it looks lush. One of the efforts to obtain this appearance is the provision of a growth regulator capable of accelerating shoot growth, namely Benzyladenine (BA). The purpose of this study was to determine the concentration of BA which produced the best effect on spatifylum growth. This research was conducted in the greenhouse of the Horticulture Building, Faculty of Agriculture, University of Lampung from July 2019 to January 2020. This research was arranged in a structured single factor treatment design consisting of six BA concentration treatments, namely 0 ppm, 10 ppm, 20 ppm, 30 ppm, 40 ppm, and 50 ppm with six repetitions. Data analysis used standard deviation which is presented in the form of a histogram by taking the average value of each treatment. The results showed that the administration of benzyladenine with concentrations 10-50 ppm tended to increase spatifylum growth in the variable leaf area, leaf greenness, tiller emergence, number of tillers, flower emergence time, and number of flowers, but had no effect on the addition of plant height and number of leaves. Giving benzyladenine with a concentration of 20 ppm was quite efficient in optimizing the vegetatif growth of spatilum, which was shown by the increase in plant height, increased number of leaves, time to emergence of tillers, and number of tillers. On the other hand, the effect of benziladenine on the generative phase requires a higher concentration, namely at a concentration of 50 ppm, the time for which the flower buds appear is the fastest and the number of flowers is the most. Keywords: Benzyladenine, Concentration, and Spatifillum.